Development of Ludo Media in Mathematics Learning on Two-Dimentional Figure in Second Grade of Madrasah Ibtidaiyah - Inayati, Isna Nurul; Islamiyah, Urfiatul (Proceedings Series of Educational Studies, 2024)
This research is motivated by the lack of innovation among educators in the development of learning media, as well as the teaching models used by teachers, which are still teacher-centered. This condition leads to students easily getting bored in learning, resulting in a decline in their interest and learning outcomes. To address this issue, the researcher developed Ludo media. This study employs a Research and Development (R&D) approach using the Borg and Gall model, which consists of 7 adjusted stages. The subjects of this research are students in class IIa of MI Al Ihsan Jeru Turen. Validity tests were conducted with experts and practitioners, followed by field trials with students. The results showed that the media expert 1 rated the media at 90%, categorized as "very suitable," while validator 2 rated it at 93.75%, also categorized as "very suitable." According to content expert 1, the media received a score of 88.3%, with the designation "suitable," while validator 2 rated it at 93.33%, with the designation "very suitable." Therefore, it can be concluded that this learning media is appropriate and valid for use with students, as evidenced by the improvement in pretest and posttest results during the field trials, with a medium group showing an increase of 56.25%.